Physical and functional properties of low temperature ground turmeric (Curcuma longa) powder: Properties of low temperature ground turmeric powder - Sapariya, P S; Joshi, N U; Dabhi, M N (Journal of Spices and Aromatic Crops, 2023)
Turmeric (Curcuma longa) rhizome (var. Salem) sample was ground according to two different grinding parameters viz., four grinding methods and two feed temperatures. The effect of grinding methods and feed temperature on some functional and physical properties was evaluated. The average values of the flow property viz., bulk density (506.78 to 537.94 kg/m3), tapped density (611.35 to 635.72 kg/m3), Hausner ratio (1.150 to 1.225) and compressibility index (13.07 to 18.34%) and functional property viz., water absorption index (3.88 to 4.46), water solubility index (16.17 to 26.51%), water holding capacity (268.40% to 307.19%) and oil absorption index (210.57% to 258.04%) with respect to different grinding methods and feed temperatures varied. The ground sample with chilled water circulation method with the ambient temperature feed (L2T0) was found the most suitable for better flow parameters and functional properties.